DOES KWL STRATEGY IMPROVE STUDENTS’ READING COMPREHENSION DURING DISTANCE LEARNING? - Anak Agung Vida Andari; Ni Wayan Krismayani; I Gde Putu Agus Pramerta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2022)
Reading cannot be separated from comprehension. Students need to comprehend what they have read to get the information. This study aimed to determine whether the subjects’ reading comprehension can be improved through the Know, Want to know, Learnt (KWL) strategy combined with pictures. The subjects were the eighth-grade students of SMP Dharma Wiweka Denpasar in the academic year 2021/2022, especially the students of the VIII H class which consisted of 36 students. Classroom action research is chosen as the design of the study. There were two cycles with two sessions in each cycle. Each cycle consists of initial reflection, planning, action, observation, and reflection. A questionnaire was also distributed to the students. Based on the result, the mean scores of pre-test, post-test 1, and post-test 2 were 51.31, 66.92, and 76.53. The result of the post-tests showed that there were significant improvements in subjects’ reading comprehension. Moreover, the questionnaire result showed that the students responded positively to using the KWL strategy combined with pictures. Therefore, this study proved that reading comprehension could be improved through KWL Strategy combined with pictures.